Perancangan Busana Magnificent Of Modular Mode - Meilinda Lenawati; Rachmawaty - (Style : Journal of Fashion Design, 2021)
Fast fashion can be interpreted as a quick response effort in providing the latest fashionable clothes according to consumer demand. This can lead to a accumulation of clothes which eventually becomes clothing waste. Clothing waste can be overcome with two opportunities, namely reuse and reduction, this reduction method uses the principle of sustainable design. Sustainable that is raised is a modular design. "Modular design" is a kind of design fashion that can not only make clothes more attractive, allow the wearer to participate in choices, increase the possibility of clothing styles, but also can extend the service cycle of clothes. In this "fast fashion" market, modular design ideas can be a breaking point, helping us find ways to balance low-carbon and eco-friendly needs and fashion. Therefore, there is a need for a ready-to-wear fashion modular design that inspires the Woloan Minahasa Stage House that can be disassembled. This will be the common thread in the creation of the work.